2016
DOI: 10.1021/acsami.6b05596
|View full text |Cite
|
Sign up to set email alerts
|

Emulsion-Based RIR-MAPLE Deposition of Conjugated Polymers: Primary Solvent Effect and Its Implications on Organic Solar Cell Performance

Abstract: Emulsion-based, resonant infrared matrix-assisted pulsed laser evaporation (RIR-MAPLE) has been demonstrated as an alternative technique to deposit conjugated polymer films for photovoltaic applications; yet, a fundamental understanding of how the emulsion target characteristics translate into film properties and solar cell performance is unclear. Such understanding is crucial to enable the rational improvement of organic solar cell (OSC) efficiency and to realize the expected advantages of emulsionbased RIR-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 48 publications
3
46
0
Order By: Relevance
“…Specifically, the sacrificial host solvent is chosen such that it absorbs the majority of the laser energy, thereby altogether avoiding the photochemical degradation of the guest polymer. Prior studies have demonstrated that the chemical structure, molecular weight, and molecular weight distribution are maintained through judicious choice of the MAPLE deposition parameters …”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the sacrificial host solvent is chosen such that it absorbs the majority of the laser energy, thereby altogether avoiding the photochemical degradation of the guest polymer. Prior studies have demonstrated that the chemical structure, molecular weight, and molecular weight distribution are maintained through judicious choice of the MAPLE deposition parameters …”
Section: Introductionmentioning
confidence: 99%
“…With its unprecedented capabilities, MAPLE has readily been exploited for growing thin polymer films for a wide range of applications including sensors, drug delivery and medical implants . Recently, promising findings have also been reported on the properties of MAPLE deposited conjugated polymer films for solar cells, organic light emitting diodes, and other organic electronic applications . Although operational devices have been made, the detailed molecular structure and the fundamental connection between processing, morphology, and transport in those devices are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have studied the morphology of so matter at mesoscopic level using the DPD method, for example, self-assembly of surfactant solutions, [30][31][32] interactions between polymers and nanoparticles 24,33,34 and phase separation for polymer solar cells. [35][36][37] The fundamental equation in the DPD method is Newton's equation of motion. Newton's equation of motion for particle i is given by:…”
Section: Dissipative Particle Dynamics (Dpd) Methodsmentioning
confidence: 99%